Main directions of transformation of the tax consulting system in Ukraine based on the EU experience - Prokopenko, Iryna Adolfivna; Ivanyshyna, Olha Stepanivna (Acta Sting, 2021)
In the article the authors consider the European experience of tax consulting. A comparative analysis of tax consulting in countries with a system of "state regulation" and a system of "self-regulation". Based on the results of the study, the authors conclude that tax consulting in Ukraine is at an early stage of development, the legal basis exists only for tax advice provided by the state tax service. The market of independent tax consulting in Ukraine has the number of unresolved issues regarding the further development of the institute of tax consulting in Ukraine. From this point of view, the need to reform domestic tax consulting is justified. Based on the generalized European experience in the regulation of tax consulting, the authors outline the key areas for the development of tax consulting in Ukraine.

У статті автори розглядають європейський досвід податкового консультування. Проведено порівняльний аналіз податкового консультування в країнах з системою "державного регулювання" та системою "саморегулювання". За результатами дослідження автори дійшли висновку, що податкове консультування в Україні перебуває на початковій стадії розвитку, законодавча база існує лише для податкових консультацій, що надаються органами державної податкової служби. Ринок незалежного податкового консультування в Україні має низку невирішених питань щодо подальшого розвитку інституту податкового консультування в Україні. З цієї точки зору необхідність реформування вітчизняного податкового консультування є обґрунтованою. На основі узагальненого європейського досвіду регулювання податкового консультування окреслено ключові напрями розвитку податкового консультування в Україні.
Keywords: tax consulting; tax culture; tax consultants; taxes; European Confederation of Tax Consultants; Union of Tax Consultants of Ukraine; податкове консультування; податкова культура; податкові консультанти; податки; Європейська конфедерація податкових консультантів; Спілка податкових консультантів України